Effect of Matcha green tea on cognitive functions and sleep quality in elderly adults with cognitive decline: a randomized controlled study over 12 months. (20th December 2022) - Uchida, Kazuhiko; Meno, Kohji; Suzuki, Hideaki; Korenaga, Tatsumi; Ito, Hitomi; Inoue, Makoto; Shan, Liu; Ota, Miho; Shiraki, Noeru; Nakamura, Shin; Yomota, Satoshi; Akinaga, Nobuyuki; et al.
Abstract: Background: Nutrition is a pivotal factor in the prevention of dementia. Matcha green tea powder, which contains L‐theanine, caffeine, and epigallocatechin gallate, has the beneficial effects of each constituent on cognitive functions and mood. However, no long‐term clinical study has yet been performed to evaluate the effect of Matcha on psychological functions. Here, we performed a randomized, double‐blinded, placebo‐controlled, clinical study, conducted over 12 months, to investigate the effect of Matcha on cognitive functions and sleep quality. Furthermore, the relationship between blood and neuroimaging biomarkers and the effect of Matcha was investigated. Methods: We recruited 939 community‐dwelling older adults aged 60–84 years and enrolled subjects with a diagnosis of subjective cognitive decline (SCD) and mild cognitive impairment (MCI). A total of 99 subjects (64 SCD, 35 MCI) were randomized, with 49 receiving Matcha (2 g/day, male 23, female 26) and 50 receiving placebo (male 20, female 30). The groups were adjusted for age, sex, and APOE 4 genotype. Cognitive functions were assessed by MMSE, MoCA, ADAS‐cog, RBANS, and the CNS Vital Signs computerized neurocognitive battery. Sleep quality was measured by the Pittsburg Sleep Quality Index (PSQI). Plasma biomarkers and neuroimaging (Amyloid PET, MRI, SPECT, fNIRS) were also assessed. The change of outcome variables from the baseline to 12‐month was tested statistically using a mixed‐effects model. Results: Compared to the placebo, the consumption of Matcha induced a significant improvement in social acuity assessed by perception of facial emotion ( P = 0.034), while continuous performance showed a trend towards improvement. The PSQI differed by 0.86 between the groups, indicating an improvement in sleep quality in the Matcha group compared to the placebo group ( P = 0.087). The MMSE score showed a slight increase in the Matcha group. Amyloid PET SUVR showed no change from baseline to 12‐month in either group, while the plasma Aβ42 was reduced in the Matcha group, suggesting increased clearance of peripheral Aβ42. Conclusion: Facial emotion recognition is impaired in cognitive impairment. This long‐term intervention study suggests that Matcha consumption can improve emotion perception and attention, and sleep quality in elderly adults with cognitive decline.